Role of myositis-specific autoantibodies in personalized therapy - Anand N Malaviya; Sanjiv Kapoor (Indian Journal of Rheumatology)
In a landmark breakthrough in 1976, Reichlin and Mattioli discovered the first myositis-specific antibody (MSA) called anti-Mi2 antibody that identified a specific clinical phenotype characterized by pathognomonic skin rash of dermatomyositis, typical proximal muscle weakness, good response to treatment, and the absence of interstitial lung disease and cancer. The discovery firmly placed inflammatory muscle diseases among the group of systemic rheumatic autoimmune diseases. Over the next four decades, a large number of additional MSAs have been discovered in this group of patients called “idiopathic inflammatory myopathy” (IIM). It is becoming clear that the increasing numbers of autoantibodies being discovered may necessitate a name change to “autoimmune myositis” (AIM), as recently suggested by a French-Canadian group. In the light of these discoveries, it was evident that a new classification system based on the combination of clinical phenotypes and the associated autoantibodies would soon be propounded. Preliminary report on such a classification was published in 2016 by the Swedish Group from Karolinska Institute led by Prof. Ingrid Lundberg. In October 2017, the European League Against Rheumatism and the American College of Rheumatology published the provisional classification criteria for IIM with the aim to categorize patients in uniform subgroups of clinical phenotype for meaningful drug trials. These are exciting times for clinicians, for research scientists, and for the patients with inflammatory myositis with reasons to be optimistic about a bright future. This short review provides a summary of the present knowledge with emphasis on its clinical implications.